Is There a Latin American University Model? - Bernasconi, Andres (International Higher Education, 2008)
Postindependence Latin American universities developed during the 19th and most of the 20th century largely under the normative influence of a Latin American idea of the university institution. In the last few decades, factors both related to the development of higher education and external to it have combined to challenge the clout of that model. As a result, notwithstanding the persistence of elements of the old paradigm, the model of the Latin American university is now related chiefly to US research universities.